Kontribusi Joglo Tani Di Mandungan Margoluwih Seyegan Sleman Yogyakarta Dalam Peningkatan Peran Pemuda Pada Pembangunan Sektor Pertanian Guna Mewujudkan Ketahanan Pangan - lailiyatus syadiah (Jurnal Ketahanan Nasional, 2015)
ABSTRACTThis study discussed about the contribution of Joglo Tani in increasing the role of youth in the development of the agricultural sector in order to achieved food resilience. This research was a qualitative-descriptive aproach. Collecting data in this study used observation, interviews, documentation, and literature study. Observation was conducted by the researcher by observing the activities of Joglo Tani, the circumstance of the agricultural performed by Joglo Tani youth. Interview was conducted with key informant, the founder of Joglo Tani, to expanded the network of informants to got another informant. Documentation was obtained from the founder, administrators, assistants, and youth of Joglo Tani in the form of a collection of the activities and products of Joglo Tani youth’s photos. A literature study was obtained from previous research relating to titles and books that supported. The results of the research showed that Joglo Tani really had big contribution in increasing the role of Joglo Tani youth, so they could be active in the agriculture sector development to achieved food resilience. The shapes of the role of Joglo Tani youth were production, promotion and marketing, as well as community empowerment. The role of Joglo Tani youth in agriculture to achieved food resilience was not always easy, but there were some obstacles encountered: (1) technical: the lack of the spirit of youth, land degradation, uncertain weather conditions, lack of cost, lack of youth-based agricultural training (2) lack of social support, (3) lack of government support. Strategic efforts undertaken by Joglo Tani youth to achieved food resilience by referring to the indicators of food resilience theory to fulfi lled food need from individual’s to country’s need both the quantity and the quality, so it could be concluded that Joglo Tani youth had contributed to achieved food resilience.ABSTRAK Penelitian ini membahas tentang kontribusi Joglo Tani dalam peningkatan peran pemuda pada pembangunan sektor pertanian guna mewujudkan ketahanan pangan. Penelitian ini merupakan penelitian kualitatif dengan pendekatan deskriptif Pengumpulan data dalam penelitian ini menggunakan observasi, wawancara, dokumentasi, dan studi pustaka. Observasi dilakukan oleh peneliti dengan mengamati kegiatan pemuda Joglo Tani, kondisi dan situasi pertanian yang dilakukan pemuda di Joglo Tani. Wawancara dilakukan dengan menemukan informan kunci yaitu pendiri Joglo Tani yang selanjutnya peneliti memperluas jaringan informan hingga mendapatkan informan lain. Dokumentasi diperoleh dari pengurus, pendamping, dan pemuda Joglo Tani berupa koleksi foto kegiatan pemuda Joglo Tani dan produk yang dihasilkan. Studi pustaka diperoleh dari penelitian terdahulu yang berkaitan dengan judul dan buku-buku yang mendukung.Hasil penelitian menunjukkan bahwa Joglo Tani sangat berkontribusi dalam peningkatan peran pemuda, sehingga pemuda Joglo Tani dapat berperan aktif dalam pembangunan sektor pertanian guna mewujudkan ketahanan pangan. Adapun bentuk peran pemuda tersebut berupa peran produksi, peran promosi dan pemasaran, serta peran pemberdayaan masyarakat. Peran pemuda Joglo Tani dalam sektor pertanian  tidak selalu mudah, namun terdapat beberapa kendala yang dihadapi yakni (1) teknis: kurangnya semangat pemuda, degradasi lahan, kondisi cuaca yang tidak menentu, minimnya biaya, minimnya pelatihan pertanian berbasis pemuda, (2) kurangnya dukungan sosial masyarakat, (3) kurangnya dukungan pemerintah. Upaya strategis yang dilakukan pemuda Joglo Tani dalam mewujudkan ketahanan pangan dengan mengacu pada indikator teori ketahanan pangan untuk memenuhi kebutuhan pangan mulai dari perseorangan sampai negara baik jumlah maupun mutunya maka dapat disimpulkan bahwa pemuda Joglo Tani telah berkontribusi mewujudkan ketahanan pangan.